Non-obstructive intracellular nanolasers - Alasdair H. Fikouras (Nature Portfolio, 2018)
While the sharp emission lines of microlasers are advantageous for cell tagging, their relatively large size can impede cell migration and behavior. Here, Fikouras et al. develop nano-sized lasers that can readily tag and track various types of cells, including through narrow constrictions.